Anaplasma Infection in Ticks in Southeastern Region of Iran - Reza Ranjbar; Mehdi Anjomruz; Ahmad Ali Enayati; Mehdi Khoobdel; Atiyeh Rafinejad; Javad Rafinejad (Tehran University of Medical Sciences, 2020)
Background: Anaplasmosis and Ehrlichiosis are the most important tick-borne diseases. This study was conducted in three cities of Kerman Province in Iran to investigate the circulation of the bacteria in ticks collected from sheep. Methods: Ticks were collected from animals using Srkj forceps and transferred to the Entomology lab in cold chain. After specimen's identification, they kept at -70 ºC. Tick DNA was extracted using Bioneers DNA extraction kits followed by Nested PCR technique to amplify ribosomal 16S rRNA gene to detect Anaplasma infection in ticks. Results: 472 sheep were examined from which 349 ticks were collected and identified in laboratory using valid keys. Tick specimens belonged to two genera and four species; Hyalomma marginatum (62.47%) was the most frequent and Hylomma asiaticum (5.73%) showed the least abundance. The infestation rate to different tick species was different in three regions of Kerman Province. Observation revealed that 24 specimens (58.3%) were positive for Anaplasma. There is a significant difference between male and female infection rate. However, there is no significant difference between these variables in each of these cities. Conclusion: This study shows high infection rates to Anaplasma in hard ticks. It is essential for health and veterinary authorities and farmers to use appropriate strategies to control ticks to reduce the infestation.